Doing It in Public: Dilemmas of Images, Voice, and Constructing Publics in Public Sociology on Sex Work. Issue 4 (9th November 2016) - Hannem, Stacey; Tigchelaar, Alex
Abstract : This study describes the use of traditional public sociology as a method of recruitment for organic public sociology research with sex workers. Drawing on their grounded research experience, the authors discuss the issues of representation and framing of the research that arise when engaging in public research with multiple stakeholder publics. Specifically, professional publics may act as gatekeepers to subaltern groups and publicly engaged research risks reproducing existing power inequities and marginalization. However, traditional public sociology can be a tool to engage with subaltern groups and to construct a public where one did not exist; here we examine the complexities, the possibilities, and pitfalls of constructing publics.